2008
DOI: 10.1007/s10856-008-3649-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun submicron bioactive glass fibers for bone tissue scaffold

Abstract: Submicron bioactive glass fibers 70S30C (70 mol% SiO(2), 30 mol% CaO) acting as bone tissue scaffolds were fabricated by electrospinning method. The scaffold is a hierarchical pore network that consists of interconnected fibers with macropores and mesopores. The structure, morphological characterization and mechanical properties of the submicron bioactive glass fibers were studied by XRD, EDS, FIIR, SEM, N(2) gas absorption analyses and nanoindentation. The effect of the voltage on the morphology of electrospu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 33 publications
0
62
0
1
Order By: Relevance
“…The mechanical properties of the scaffolds obtained from 70S30C nanofibers were measured by nanoindentation. It was found that the elastic modulus of the scaffold was close to that of trabecular bone [57].…”
Section: Sol-gel Techniquesmentioning
confidence: 83%
See 2 more Smart Citations
“…The mechanical properties of the scaffolds obtained from 70S30C nanofibers were measured by nanoindentation. It was found that the elastic modulus of the scaffold was close to that of trabecular bone [57].…”
Section: Sol-gel Techniquesmentioning
confidence: 83%
“…Similarly to conventional sol-gel synthesis, sol-gel derived and electrospun fibers must be submitted to heat-treatment to remove organic additives. Electrospinning of sol-gel precursors can result in bioactive glass fibers with diameters < 100 nm [55][56][57]. The diameter and the morphology of the nanofibres can be controlled to some extent by the amount and type of additive and the applied electric field.…”
Section: Sol-gel Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, among the different techniques used to produce BG-polymer composites [1,11,13], up to now, electrospinning has only been applied with sodium-free bioactive glass [27][28][29][30][31][32][33][34]. Usually, the electrospinning solution was obtained by mixing a solgel precursor of BG with a polymer solution.…”
Section: Introductionmentioning
confidence: 99%
“…The flying time of the jet should thus be long enough to enable its complete drying out. Fibers are deposited either as random or aligned mats, by using immobile or rotary collectors respectively [168,169].…”
Section: Electrospinningmentioning
confidence: 99%